Big Data, open information for technology transfer - Ponte, Ana (2018)
The management of information is currently subject to legal restrictions, particularly information relating to generated knowledge enhancing economic advantage, as the one registered in patents. Such legal restrictions derive from a classical concept of the innovation cycle, which provides a basis for the current parameters of Science funding and commercial exploitation of technological development and innovation results. Open innovation, as a new model of innovation management, brings along inherent challenges – at legal, cultural and organizational levels - to the classical model of the innovation cycle. This paper describes a discussion session that has disclosed specific cases of open innovation implementation, based on the use of big data extracted from patents. Upon the findings of that working session, it intends to showcase the benefits that open innovation based on patent data can bring to sustainable development, likely to represent large social and economic gains, and which may, therefore, justify a proactive approach to the resolution of the mentioned challenges, in particular as regards the drafting of open innovation strategies. Alongside, big data processing tools already in development, as also illustrated herein, provide assurance as to the validation of this form of innovation to solve specific social problems.